2012
DOI: 10.1088/1674-1056/21/8/086401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two-dimensional shear flow on the stability of a crystal interface in a supercooled melt

Abstract: A model is developed based on the time-related thermal diffusion equations to investigate the effects of two-dimensional shear flow on the stability of a crystal interface in the supercooled melt of a pure substance. Similar to the three-dimensional shear flow as described in our previous paper, the two-dimensional shear flow can also be found to reduce the growth rate of perturbation amplitude. However, compared with the case of the Laplace equation for a steady-state thermal diffusion field, due to the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When proceeding to the higher-order terms, we obtain the asymptotic solution in Eqs. ( 10)- (12). It is noticed that the solution obtained in Eqs.…”
Section: Asymptotic Solutionmentioning
confidence: 88%
See 1 more Smart Citation
“…When proceeding to the higher-order terms, we obtain the asymptotic solution in Eqs. ( 10)- (12). It is noticed that the solution obtained in Eqs.…”
Section: Asymptotic Solutionmentioning
confidence: 88%
“…[7] Though various experimental observations and numerical simulations explicitly suggest the significant effect of the convection on the interface microstructure formation, theoretical investigations of the morphological evolution of interface during crystallization in the stirred melt and solution are still very limited due to the complicated effects of convection. [2,[8][9][10][11][12][13][14][15][16][17] Hence, there is a strong need for the common analytical method to predict the experimentally observed particle morphologies developed under different flow conditions. A feasible way is to model the growth of spherical particles in the complex flow of the stirred liquid as a singularly perturbed free boundary problem and find its asymptotic solution by using the matched asymptotic expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…Buchholz and Engler [8] found that the deformation of the solute layer around the dendrites tips caused by the forced convection makes the columnar dendrites tips incline in the upstream direction. [9,10] In the solidification, the crystal growth will be affected by many factors, such as undercooling, [11] interface kinetics, [12] anisotropic surface tension, [13,14] flow, [15][16][17][18][19] etc. These experiments and numerical simulations deepen the understanding of the crystal growth.…”
Section: Introductionmentioning
confidence: 99%